Female advantage? Management and financial performance in microfinance - Sigurður Guðjónsson; Kari Kristinsson; Haukur Freyr Gylfason; Inga Minelgaite (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The purpose of the article is to investigate whether female presence in microfinance institutions' management team, i.e. board members, managers and loan officers, will improve their financial performance. We combine financial data on MFIs that is available from the MIX Market database with original data on the gender composition of MFIs' management team, who include board members, managers and loan officers. This original dataset of 223 MFIs is analyzed using Logit-Tobit regression models with return on assets (ROA) as the dependent variable and proportion of female board members, female loan officers and female managers as the main independent variables. We find that a higher proportion of female managers and female loan officers improve financial performance in microfinance, while a higher proportion of female board members does not. Our results indicate that a major contributor to the financial sustainability of microfinance institutions is having a higher rate of women in vital decision-making roles, especially lower level management positions.
Keywords: G21; L31; M14; 650; microfinance; gender; management; financial performance; firm